2019
DOI: 10.1002/erv.2677
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and depressive symptoms are related to core symptoms, general health outcome, and medical comorbidities in eating disorders

Abstract: Objective The goal of this study is to identify potential factors that have a significant effect on anxiety and depression of patients with eating disorders (ED) using the beta‐binomial regression (BBR) approach on a broad sample of patients. Method This cross‐sectional study involved 520 ED patients. The effect of sociodemographics, core symptoms, general health outcomes, and medical comorbidities in anxiety and depression were analysed jointly using the beta‐binomial mixed‐effects model. Results Two hundred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 47 publications
3
22
0
5
Order By: Relevance
“…We can hypothesize that high segregation plays a protective role in AN, since it probably allows a more efficient cognitive processing, but we can also speculate that a lower integration may predispose to higher anxiety symptoms in the disorder. This finding supports the importance of therapeutically addressing anxiety symptoms when they occur in comorbidity with AN (Lloyd et al, 2019; Martín et al, 2019).…”
Section: Discussionsupporting
confidence: 78%
“…We can hypothesize that high segregation plays a protective role in AN, since it probably allows a more efficient cognitive processing, but we can also speculate that a lower integration may predispose to higher anxiety symptoms in the disorder. This finding supports the importance of therapeutically addressing anxiety symptoms when they occur in comorbidity with AN (Lloyd et al, 2019; Martín et al, 2019).…”
Section: Discussionsupporting
confidence: 78%
“…Regarding the psychological features, depression and anxiety scores were significantly higher in the long-term group. A cross-sectional study revealed that depression and anxiety were related to eating disorder symptoms and anxiety was related to older age [40]. Thus, older age might have been a factor related to high anxiety in the current study.…”
Section: Discussionmentioning
confidence: 69%
“…Similarly to autism, eating disorders are frequently found to be comorbid with anxiety (Bulik et al 1997 ; Griffiths et al 2019 ; Hudson et al 2007 ; Martín et al 2019 ) and depressive disorders (Griffiths et al 2019 ; Hudson et al 2007 ; Martín et al 2019 ). Anorexia nervosa (AN) and bulimia nervosa (BN), but not binge-eating disorder (BED), also exhibit marked sex/gender differences in their prevalence.…”
Section: Introductionmentioning
confidence: 99%